Global economic developments 2000-2001 (ECLAC SantiagoCL, 2002)
Analyzes the most significant developments that have taken place in 2000-2001 with a view to providing an overall picture of the international context facing Caribbean economies in the short run.
Keywords: ECONOMIC DEVELOPMENT